PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN SUMUR RESAPAN BIOPORI DI KELURAHAN SUKARAMI KOTA BENGKULU (Universitas Bengkulu, 2024)
Biopore holes are a practical technology for water conservation and retention, allowing rainwater to seep into the ground through specifically sized holes. This method aims to reduce surface flooding caused by rain runoff, while also retaining and transferring water to underground reservoirs. Additionally, it is cost-effective, easy to create, and multifunctional, as it helps manage waste and produce compost. Biopore holes can be implemented in residential areas, yards, or fields, making it particularly suitable for densely populated urban neighborhoods. One way to promote this is through educational outreach using visual aids in areas prone to flooding and waste accumulation, encouraging the use of affordable, effective, multifunctional, and environmentally friendly technologies. The outreach has already been conducted in Sukarami Village, aiming to enhance residents' understanding of independently creating biopore holes and their multiple ecological benefits. Keywords: infiltration wells, biopores, appropriate technology.